Double-Diffusive Convection of Synovial (Couple-Stress) Fluid in the Presence of Hall Current Through a Porous Medium - M. Singh (International Journal of Applied Mechanics and Engineering, 2018)
An investigation made on the effect of Hall currents on double-diffusive convection of a compressible synovial (couple-stress) fluid in the presence of a horizontal magnetic field through a porous layer is considered. The analysis is carried out within the framework of linear stability theory and normal mode technique. A dispersion relation governing the effects of viscoelasticity, compressibility, magnetic field and porous layer is derived. For the stationary convection, a synovial fluid behaves like an ordinary Newtonian fluid due to the vanishing of the viscoelastic parameter. The stable-solute gradient, compressibility, and magnetic field have postponed the onset of convection, whereas Hall currents and medium permeability have not postponed the onset of convection, moreover, a synovial fluid has a dual character in the presence of Hall currents, whereas in the absence of Hall current in synovial fluid have postponed the onset of convection, which is in contrast in case of thermal convection couple-stress fluid with same effects. These analytic results are confirmed numerically and the effects of various parameters are depicted graphically. It has been observed that oscillatory modes are introduced due to the presence of viscoelasticity, magnetic field, porous medium and Hall currents which were non- existent in their absence. The sufficient conditions for the non-existence of overstability are also obtained.